Sistem Pemandian dan Pembersihan Sangkar Burung Murai Batu Otomatis Berbasis Internet Of Things - Savitri, Valiyana; Puteri Novani, Nefy (CHIPSET, 2024)
This study designs an automated bathing and cage cleaning system for Murai Batu birds based on the Internet of Things (IoT) using the NodeMCU ESP32 microcontroller. The system integrates a turbidity sensor to monitor water clarity, an ultrasonic sensor to measure water level, and a load cell sensor to detect waste weight. Additionally, a PIR sensor is used to detect the bird's presence, while a stepper motor and relay are employed to automate the opening and closing of the door. Cage cleaning is performed by operating a belt conveyor driven by a DC motor, and water replacement is conducted using a water pump. All components are controlled by the NodeMCU ESP32, with monitoring facilitated through the Telegram application. The implementation results demonstrate that the system is effective, achieving sensor accuracies of 95.4%, 97.7%, and 97.36%, respectively, and providing convenience for bird owners in managing and monitoring the system remotely.